Sacubitril/valsartan in real-life European patients with heart failure with reduced ejection fraction: a systematic review and meta-analysis. (25th November 2020) - Giovinazzo, S; Carmisciano, L; Toma, M; Sormani, M.P; Canepa, M; Senni, M; Porto, I; Ameri, P
Abstract: Background: Real-world data are needed to gauge how a therapy is implemented in clinical practice. Methods: We systematically reviewed the abstracts presented at international congresses and the peer-reviewed original research articles, which described the use of sacubitril/valsartan in European patients with HFrEF from Sep 2014 until Nov 30, 2019. Meta-analysis estimates were combined using a random effects model with inverse variance weights. Results: 15 abstracts and 11 articles, including 14, 179 patients, were selected. Except for a study that evaluated 12, 082 (85, 2%) subjects, the sample size was 28 (0.2%) to 1, 120 (7.9%) patients. Taking as reference PARADIGM-HF, few baseline characteristic were reported for >80% of the pooled population (Table), while all other ones were available for 12% of subjects or less (Figure). Underreporting was less common for articles than for abstracts (OR 0.42, 95% CI: 0.20–0.91). Compared with the patients enrolled in PARADIGM-HF, those in real-life were older and more likely to being previously treated with ARB, MRA and diuretics (Table). NYHA class III-IV (OR 2.39, 95% CI: 1.58–3.59; I2=92%), ICD (OR 4.21, 95% CI: 2.31–7.69; I2=93%) and CRT (OR 4.53, 95% CI: 3.89–5.27; I2=0%) were also more likely, while a history of hypertension was less frequent (OR 0.61, 95% CI: 0.42–0.87; I2=82%). The monthly achievement rate of the full dose of sacubitril/valsartan was 6%. When follow-up was ≥6 months, the percentage of subjects reaching the full dose was about 40% and very homogenous. Age and full dose attainment were inversely related (β −2.71, 95% CI: −5.3 to −0.1). All cause-mortality and hospitalization rates were 6/100 person-year (9 studies, 1046 patients) and 25/100 person-year (5 studies, 775 patients), respectively. Conclusions: With the limitation of being heterogeneous and of overall low quality, the literature suggests that, in Europe, sacubitril/valsartan is prescribed to patients with somehow more severe HFrEF than in the pivotal trial, who most often do not reach the full dose. Funding Acknowledgement: Type of funding source: None